2013
DOI: 10.1021/la402053a
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Transition of Micelle–Vesicle–Micelle in a Mixture of Cationic Surfactant and Anionic Surfactant-like Ionic Liquid: A Pure Nonlipid Small Unilamellar Vesicular Template Used for Solvent and Rotational Relaxation Study

Abstract: The micelle-vesicle-micelle transition in aqueous mixtures of the cationic surfactant cetyl trimethyl ammonium bromide (CTAB) and the anionic surfactant-like ionic liquid 1-butyl-3-methylimidazolium octyl sulfate, [C4mim][C8SO4] has been investigated by using dynamic light scattering (DLS), transmission electron microscopy (TEM), surface tension, conductivity, and fluorescence anisotropy at different volume fractions of surfactant. The surface tension value decreases sharply with increasing CTAB concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 65 publications
4
93
1
Order By: Relevance
“…The anisotropy decays of C-153 in 20 mM NaDC in the presence of different wt% of [bmim]-BF 4 are shown in Fig. 72 The fast component of the decay remains almost constant with increasing concentration of IL and the slow component increases gradually with increasing concentration of IL and as a result, the average rotational relaxation time also increases. Bhattacharyya et al determined the time resolved anisotropy decays of C-153 by varying the excitation wavelengths and they showed that the anisotropy decays do not show any appreciable dependence on excitation wavelength.…”
Section: Time Resolved Anisotropy Measurementsmentioning
confidence: 98%
“…The anisotropy decays of C-153 in 20 mM NaDC in the presence of different wt% of [bmim]-BF 4 are shown in Fig. 72 The fast component of the decay remains almost constant with increasing concentration of IL and the slow component increases gradually with increasing concentration of IL and as a result, the average rotational relaxation time also increases. Bhattacharyya et al determined the time resolved anisotropy decays of C-153 by varying the excitation wavelengths and they showed that the anisotropy decays do not show any appreciable dependence on excitation wavelength.…”
Section: Time Resolved Anisotropy Measurementsmentioning
confidence: 98%
“…In bulk water, C153 molecule exhibits single exponential decay profile with reorientation time of ∼100 ps. 18 Figure 5b and the corresponding fitted parameters are given in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 contribution of 17%). In C 16 …”
Section: Time-resolved Anisotropy Measurementsmentioning
confidence: 99%
“…[9][10][11][12] In aqueous solution, the transition from micelle to vesicle is commonly influenced by various external stimuli; therefore this has been executed by variation in the ratio of cationic and anionic surfactants, polar additives, temperature, salts etc. [13][14][15][16][17][18][19][20][21] The morphology of the aggregates sometimes depends on the nature of additives. 14,[22][23][24][25] Considering the influence of organic additive in aggregate transition, we have been motivated to study micelle-elongated micelle-vesicle transition using room temperature ionic liquids as amphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…The probe DPH is mostly used in such measurements [60]. Being hydophobic, DPH should prefer the hydrophobic environment of the aggregates.…”
Section: Fluorescence Anisotropy Studymentioning
confidence: 99%